Better Service Delivery for Inclusive Growth in the Dominican Republic (OECD Public Governance Reviews, 2017)
This Review focuses on improving access to quality and timely services for citizens as a means to facilitate inclusive growth in the Dominican Republic. Despite its macroeconomic performance in the last decade, poverty and levels of inequalities remain high in the Dominican Republic. At the same time, citizens report limited satisfaction with the quality and access to services in the country, often reflected in less than optimal outcomes in areas such as health, transport or education. The review's focus on service delivery offers the opportunity to apply the concepts and tools of public governance at an operational level and with immediate implications for the government-citizen relationship. The inclusion of multidisciplinary good practices, collected through OECD work on public sector management, digital government, innovation or administrative simplification, allows a comprehensive but integrated assessment of the use of public policy levers for optimizing service design and delivery. By covering aspects relating both to the competence of government – in terms of the quality, timeliness and effectiveness of public services – and to the principles governing the provision of services – including engagement, accountability or inclusiveness, this review identifies policy recommendations to improve access, coverage and quality of public services, regardless of income levels, location and other social and economic factors – as a key lever to achieve more inclusive growth